PERILAKU KESEHATAN MASYARAKAT TERHADAP KEJADIAN DIARE BERDASARKAN ASPEK SANITASI LINGKUNGAN DI KABUPATEN BARITO KUALA - Megasari Megasari; Taufik Hidayat; Gusti Chairuddin; Imam Santoso (EnviroScienteae, 2015)
Health problem is a very complex of inter-related with other issues beyond health itself. Diarrhea is one of environment-based disease remains a problem in Indonesia. Knowing the relationship between the research goals of public health behaviors with the incidence of diarrhea and explain behavior (knowledge, attitudes, actions) on the incidence of diarrhea public health in Barito Kuala regency. With a sample of 114 households. to analyze factors that determine the behavior of public health such as the incidence of diarrhea used chi square analysis. The results showed that the respondents were knowledgeable good (31.6%), adequate (56.1%), less (12.3%), respondents who behave well (13.2%), adequate (83.3%), less (3.5%) and respondents with both measures (34.3%), adequate (38.6%), less (27.1%). There is a relationship between the incidence of diarrhea location p-value 0.016, no knowledge of the relationship with the incidence of diarrhea p-value of 0.000, there was no correlation with the incidence of diarrhea attitude p-value 0.129. The relationship between the action with diarrhea p-value 0.002 and the relationship between the incidence of health behavior based on environmental sanitation aspects of the p-value of 0.024